A New Opportunity for 2D van der Waals Heterostructures: Making Steep‐Slope Transistors. Issue 2 (28th November 2019) - Lyu, Juan; Pei, Jing; Guo, Yuzheng; Gong, Jian; Li, Huanglong
Abstract: The use of a foreign metallic cold source (CS) has recently been proposed as a promising approach toward the steep‐slope field‐effect‐transistor (FET). In addition to the selection of source material with desired density of states–energy relation ( D ( E )), engineering the source:channel interface for gate‐tunable channel‐barrier is crucial to CS‐FETs. However, conventional metal:semiconductor (MS) interfaces generally suffer from strong Fermi‐level pinning due to the inevitable chemical disorder and defect‐induced gap states, precluding the gate tunability of the barriers. By comprehensive materials and device modeling at the atomic scale, it is reported that 2D van der Waals (vdW) MS interfaces, with their atomic sharpness and cleanness, can be considered as general ingredients for CS‐FETs. As test cases, InSe‐based n‐type FETs are studied. It is found that graphene can be spontaneously p‐type doped along with slightly opened bandgap around the Dirac‐point by interfacing with InSe, resulting in superexponentially decaying hot carrier density with increasing n‐type channel‐barrier. Moreover, the D ( E ) relations suggest that 2D transition‐metal dichalcogenides and 2D transition‐metal carbides are a rich library of CS materials. Graphene, Cd3 C2, T‐VTe2, H‐VTe2, and H‐TaTe2 CSs lead to subthreshold swing below 60 mV dec −1 . This work broadens the application potentials of 2D vdW MS heterostructures and serves as a springboard for more studies on low‐power electronics based on 2D materials. Abstract : 2D materials are predicted to be a rich library of cold‐source (CS) materials. Transistors based on 2D metallic CS material:2D semiconducting channel material van der Waals (vdW) heterostructures can have steep subthreshold‐slopes below 60 mV dec −1 because of the multiple inherent advantages of the 2D vdW heterostructures, namely desired density‐of‐states–energy relations and gate‐tunable barrier heights.